Role of hysteroscopic techniques in the treatment of female genital pathology - Suskic, Amer; Opric, Dejan; Suskic, Sanela Halilovic; Nikolic, Gorana; Filipovic, Isidora; Fazlic, Alina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Hysteroscopy is the process of viewing and operating in the endometrial cavity from a transcervical approach. A camera is commonly attached to the proximal end of the hysteroscope to broadcast the image onto a large video screen. The development of hysteroscopy is rooted in the work of Pantaleoni, who first reported uterine endoscopy in 1869. However, at that time, instrumentation was elementary, and expansion of the uterine cavity was insufficient. In 1925, Rubin first used CO2 to distend the uterus. The use of liquid distention media became routine by the 1980s, and many new hysteroscopic procedures, including endometrial ablation, were developed. Methods: This was a retrospective study which presents the results of hysteroscopic treatment of various gynecological diseases in Cantonal hospital Travnik, Bosnia and Herzegovina in the period from 2011 to 2019. Total 175 cases were enrolled. All underwent hysteroscopic surgery in general anesthesia. The results were statistically analyzed. Results: Total number of patients is 175. The incidence is highest in the age 31-50 years (62%). Endometrial polyp is the most common pathological condition in 80%, myoma submucosum in 5,7%, and septum uteri 2,8%. The most common treatment was polypectomy 80%, then resection of submucosal myoma 5,7%, and extraction of IUD 4%. Conclusions: Hysteroscopy involves a minimal damage to body tissues. It is safer than open surgery. Hysteroscopic treatment has contributed to faster treatment, faster recovery and reducing the cost of treatment, and thus raise the level of efficiency.